2010
DOI: 10.1121/1.3384695
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into and modelling of head movement for objective evaluation of the spatial impression of audio.

Abstract: Research was undertaken to determine the nature of head movements made when judging spatial impression and to incorporate these into a system for measuring, in a perceptually relevant manner, the acoustic parameters which contribute to spatial impression: interaural time and level differences and interaural cross-correlation coefficient. First, a subjective test was conducted that showed that (i) the amount of head movement was larger when evaluating source width and envelopment than when judging localization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…However, this information is essential in order to determine the range and pattern of head positions that should be taken into account when capturing suitable binaural signals for analysis. An experiment that examined this is briefly described, and readers are referred to the original publications 11,12 for further information.…”
Section: Investigation Of Head Movements Made By Listenersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this information is essential in order to determine the range and pattern of head positions that should be taken into account when capturing suitable binaural signals for analysis. An experiment that examined this is briefly described, and readers are referred to the original publications 11,12 for further information.…”
Section: Investigation Of Head Movements Made By Listenersmentioning
confidence: 99%
“…To investigate the difference in the performances of these two models in more detail, the authors designed another set of experiments where the physical parameters related to spatial impression were measured and compared. The results are summarised below, and more information can be found in the original publications 13,12 .…”
Section: Investigation Of Multi-position Binaural Capture Devicesmentioning
confidence: 99%
“…It is known that head motion facilitates sound source localization and improves localization accuracy (Thurlow et al, 1967; Mackensen, 2004; Honda et al, 2013) and helps to resolve front-back ambiguities (Pöntynen & Salminen, 2019). Kim et al (2013) observed that listeners move their heads over a wider range when judging source width and listener envelopment than for sound source localization. For the evaluation of timbre, the range of head rotation in azimuth was very low compared to the other tasks.…”
Section: Formation Of the Listener’s Expectationmentioning
confidence: 99%
“…The current experiments focus on small head rotations (10 • ) along the yaw axis. Small head movements have been shown to comprise the majority of natural head movements [17], and can be considered, if necessary, as a first step in a more complex movement framework. An added benefit of small rotation angles is that they allow us to approximate the rotation with a single axis and a constant acceleration.…”
Section: Introductionmentioning
confidence: 99%